Developing pandemic preparedness in Europe in the 21st century: experience, evolution and next steps - Angus Nicoll; Caroline Brown; Franz Karcher; Pasi Penttinen; Michala Hegermann-Lindencrone; Silvia Villanueva; Massimo Ciotti; Lucie Jean-Gilles; Sybille Rehmet; Jonathan S Nguyen- (The World Health Organization, 2012)
PROBLEM: Improving pandemic planning and preparedness is a challenge in Europe, a diverse region whose regional bodies (the Regional Office for Europe of the World Health Organization [WHO], the European Commission and the European Centre for Disease Prevention and Control) have overlapping roles and responsibilities. APPROACH: European pandemic preparedness indicators were used to develop an assessment tool and procedure based on the 2005 global WHO checklist for pandemic preparedness. These were then applied to Member States of WHO's European Region, initially as part of structured national assessments conducted during short visits by external teams. LOCAL SETTING: Countries in WHO's European Region. RELEVANT CHANGES: From 2005 to 2008, 43 countries underwent a pandemic preparedness assessment that included a short external assessment visit by an expert team. These short visits developed into a longer self-assessment procedure involving an external team but "owned" by the countries, which identified gaps and developed plans for improving preparedness. The assessment tool and procedure became more sophisticated as national and local pandemic preparedness became more complex. The 2009 pandemic revealed new gaps in planning, surveillance communications and immunization. LESSONS LEARNT: Structured national self-assessments with support from external teams allow individual countries to identify gaps in their pandemic preparedness plans and enable regional bodies to assess the regional and global resources that such plans require. The 2009 pandemic revealed additional problems with surveillance, pandemic severity estimates, the flexibility of the response, vaccination, involvement of health-care workers and communication. European national plans are being upgraded and global leadership is required to ensure that these plans are uniformly applied across the region.